The Female Standard:: Evaluating Cultural Expectations for Women in Scripture and Politics - Laura Tringali Sobieski (Lumen et Vita, 2020)
The year 2020 has made plain many injustices present in the systems and worldviews of American society. In a divisive election year, the factor of “electability” was of key importance in the effort to nominate a candidate to oppose the sitting President. In considering the question “Where do we go from here?”, we ought to wrestle with our communal decision that the female candidates vying for the Democratic nomination were categorically unelectable or less electable simply because of their femaleness. This paper seeks to explore how interpretation of our Scriptures has played a role in sustaining the societal structures which foster inequality. And, more importantly, how our Scriptures can fruitfully be interpreted to validate female leadership. Using the example of the story of Martha and Mary in the Gospel of Luke, this paper will problematize modern readings that have created a culture of devaluing female leadership. The history of interpretation of the story of Martha and Mary has evolved in many phases, the most relevant being that interpretation has narrowed from a story of discipleship for all Christians to a story that only has meaning for women. Reflecting on both Scripture and current gender studies commentary, this paper will call into question the unreasonable expectations of American women and consider where we ought to go from here.